Evaluation of seismic risk of buildings through vulnerability functions in the city of Ayacucho – Peru - Sulca-Huaman, Jhunior (2022)
Peru is one of the countries most exposed to catastrophic events worldwide such as: floods, debris flow, tsunamis, earthquakes. Particularly, earthquakes are generated by the interaction of the Nazca and South American plates known as the subduction process and shallow faults. Likewise, another major problem that Peru is going through is informality in construction, which, added to a large earthquake, could bring with it great economic losses and human lives. Therefore, these problems have motivated the development of this research, which aims to evaluate the seismic risk of buildings in the district of Ayacucho - Peru. In this sense, the probabilistic seismic threat is evaluated using the R-CRISIS program, accompanied by geophysical studies such as MASW (Multichannel Analysis of Surface Waves) that allow the soil to be characterized based on shear wave velocities. Furthermore, the seismic vulnerability of buildings is evaluated using the vulnerability index method, which is based on eleven essential parameters that characterize the susceptibility of buildings to damage after the occurrence of an earthquake. Finally, the evaluation of seismic risk is carried out through the use of vulnerability functions and the results are reflected in representative maps for different seismic scenarios, which are prepared using Geographic Information Systems (GIS). The results show great economic losses and human lives that would be caused by different seismic intensities in the Ayacucho district. Furthermore, more than 50% of buildings could suffer heavy or severe damage during the occurrence of a rare earthquake whose return period is 475 years.